Paradigma Holistik Hukum Progresif - . Faisal (Universitas Bandar Lampung (UBL), 2010)
Positivism paradigm is one of the legitimacy of science, that still survive in the scienceof law, but several decades of this legal positivism get criticism of new ideas, example:progressive law by Satjipto Rahardjo, with maxim “law for man, not man for law”.The holistic paradigm of progressive law has lies in consillience, that is contained thevalue of unification model (human beings as the dominant actors on the legal realities)and firmly united model (as effort to liberated from positivism paradigm). Holisticparadigm that accompanies the progressive legal ideas, include: the law as a dynamicinstitution, the law as a doctrine of humanity and justice, the law as regulatory andbehavior aspects, the law as a doctrine of liberation. With a holistic paradigm,progressive law exists to spread the goodness, prosperity, justice and peace.